The Correlation between Caries and Quality of Life of Mentally Disabled Learners (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Introduction.Â Mentally disabled learners have dental problems 30% more complex than the ordinary toddler. It is because they have intellectual function disorder and adaptive behavior. This condition caused limitations in cleaning teeth optimally. So it will increase the risk of caries. This study objective is to find the correlation between the quality of life and dental caries at mentally disabled learners. Method. An analytical observational study with a cross-sectional approach to 118 learners in Sidoarjo, Indonesia, by total sampling. The variables in this study were quality of life (was measured with WHOQL-BREF index) and dental caries (was measured with DMF-T index). Tools and materials used are dental kids, alcohol 70%, cotton pellet, cotton roll, tampon, and WHOQL-BREF sheet. The data were presented descriptively in the form of a frequency distribution table, continued by Spearman Correlation test to analyze the correlation between the quality of life and dental caries at mentally disabled learners. Results. Most of the respondents are male (61%), with a range of age is 16-20 years old. The average quality of life for mentally disabled learners is the moderate category ( 65%). The average dental caries is considered as high. Spearman correlation shows pâ‰¤Î±(0,05) means there is a correlation between dental caries and quality of life. Conclusion. There is a correlation between dental caries and the quality of life for mentally disabled learners.